Food insecurity, morbidity, and susto: Factors associated with depression severity in Guatemala measured with the Personal Health Questionnaire 9. (December 2022) - Maupin, Jonathan; Hackman, Joseph
Background: Depression is the largest contributor to non-fatal health loss globally and the majority of this burden occurs in low- and middle-income countries. Yet, estimates of prevalence rates and severity in these contexts may be uncertain due to limited screening, lack of mental health providers, and stigma around mental disorders which may prevent individuals from seeking care. In Guatemala, estimates of depression vary, due in part to the range of screening and diagnostic instruments used and diversity of sample populations. Most studies emphasize personal experiences with violence as a predictor of depression in Guatemala, although high rates of inequality, discrimination, and resource scarcity in the country potentially play a role. Aims: In this study, we examine factors associated with depression severity categories measured with the Personal Health Questionnaire 9 (PHQ-9) among a random sample of women in a small urban community in the Central Highlands of Guatemala. Methods: Participants were recruited through a randomized sample of households in a small urban community. Participants completed a questionnaire which included questions on demographics, illness history, food insecurity, and the PHQ-9. In total, 101 women were included in the analysis. Results: Food insecurity, 2-week symptom reporting, and experiencing susto are associated with higher depression severity categories. Conclusion: This research highlights need for more research on factors related to the prevalence and severity of mental disorders, and the relationship between mental disorders and cultural constructs of distress, particularly in areas like Guatemala with limited mental health services.